Halogen-induced core structural evolution of four dinuclear copper(i) luminescent coordination compounds. Issue 34 (15th August 2022) - Li, Na; Tan, Chunhong; Feng, Yi; Cheng, Lu; Cao, Meng; Sun, Yunkai; Wang, Xiao-Feng
Abstract : Four luminescent di-copper(i ) coordination complexes have been prepared and characterized, which reveal two kinds of Cu2 -core structural configurations induced by differently sized halogen anions. Abstract : The reactions of [Cu(CH3 CN)4 ]ClO4 and 2-(diphenylphosphino)pyridine (dppy) with different halogen reagents NH4 X (X = Cl −, Br − and I − ) and four luminescent di-copper(i ) coordination compounds, namely [Cu2 (μ-dppy)3 Cl]ClO4 ·H2 O (1a ), [Cu2 (μ-dppy)3 Br]ClO4 (2a ), Cu2 (μ-Br)2 (μ-dppy)(η-dppy)2 (2b ) and [Cu2 (μ-I)2 (μ-dppy)(η-dppy)2 ] (3b ), were isolated. Intriguingly, X-ray crystallographic studies reveal that there were two kinds of Cu2 -core structural configuration induced by the differently sized halogen anions. With Cl − acting as a co-ligand, 1a featured a trefoil-like Cu2 -core with three μ2 -dppy in a head-to-head orientation bridging two Cu(i ) and one terminal Cl − occupying one axial position. On replacing Cl − with I −, 3b comprised a butterfly-like Cu2 -core, being bridged by two I − anions and one μ2 -dppy along with two terminal dppy. When Br − was employed, both the above types of Cu2 -cores were obtained in 2a and 2b, respectively. All these four di-copper(i ) compounds exhibit intense green photoluminescence with microsecond lifetimes.